Improving Mathematics Learning Result By Applying The Discovery Learning Model And The Utilization of ICT- Based Multimedian - Desy Haryani Handresmawati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in mathematics muple class III elementary school with discovery learning model using ICT-based multimedia. The research conducted was a Classroom Action Research (PTK) in three cycles. In the first cycle, students who completed the evaluation were 52%. In the second cycle, students who completed after evaluating wre 76%. In cycle III the students who completed after carrying out the post test were 94%. These results indicate that the discovery learning model with the use of  ICT-based multimedia can improve student learning outcomes, especially Class III mathematics muple at SDN Kedalon 01, Batangan District, Pati Regency.